Freezing of epididymal canine sperm with centrifuged egg yolk - Restrepo B., Giovanni (2017)
The aim of this research was to evaluate the use of centrifuged egg yolk (CEY) in the freezing process of canine epididymal spermatozoa. Testicular-epididymis complexes (TECs) were obtained after the orchiectomy of 20 domestic dogs (Canis familiaris) of different breeds and with an age range between 1 and 6 years. The tail of the epididymis was dissected and spermatozoa were obtained by the retrograde flow technique. The spermatozoa were divided into two aliquots and extended in Triladyl® supplemented with 10% CEY (CEY10) or 20% CEY (CEY20). Semen freezing was performed using a standard protocol with liquid nitrogen vapors and semen was packed in straws of 0.5 ml. A computerized system was used to evaluate the motility, kinetics and concentration of spermatozoa. In addition, post-thawing sperm vitality (VE), abnormal morphology (MA) and plasma membrane integrity (HOS) were evaluated. Statistical analysis was performed by adjusting generalized linear models (GLM) and comparing means by the Tukey test. For CEY10 higher values for linear (VSL), curvilinear (VCL) and mean (VAP) velocities were found compared to CEY20 (p<0.05). There were no differences related to the concentration of CEY for other parameters as motility, sperm kinetics, VE, MA and HOS. It is concluded that CEY can be used as supplement for the freezing process of canine epididymal semen. Additionally, when the CEY is used in a proportion of 10% of the extender, it favors the post-thawing sperm kinetics.